Optimization of a commercial Histoplasma galactomannan EIA test in a population from an endemic area of histoplasmosis in southern Brazil. Issue 4 (25th December 2022) - Blan, Bianca dos Santos; Poester, Vanice Rodrigues; Basso, Rossana Patricia; Benelli, Jéssica Louise; Sanchotene, Karine Ortiz; Caceres, Diego H.; Doherty, Brian; Pasqualotto, Alessandro Comarú; Xavier, Melissa Orzechowski
Abstract: Background: Since 2020 the World Health Organization (WHO) recommends Histoplasma antigen detection for the diagnosis of disseminated histoplasmosis (DH) in people living with HIV (PLHIV). Objective: Here we aimed to optimise the IMMY's Clarus® Histoplasma GM enzyme immunoassay (EIA), evaluating the best cut‐off in the semi‐quantitative (SQ‐HGM EIA), also known as 'calibrator cut‐off procedure'. Methods: The optimization was done using the quantitative standard procedure (Q‐HGM EIA), also known as 'standard curve procedure', as reference test. A retrospective study from an endemic area of DH in southern Brazil was carried out including 264 patients investigated for DH using the test. Receiver Operator Characteristic curve was plotted, and sensitivity and specificity of the SQ‐HGM EIA were calculated. Results: The study included 24 positive (values ≥ 0.20 ng/ml) and 240 negative patients by the Q‐HGM EIA. According to the manufacturer SQ‐HGM EIA protocol, the new SQ‐HGM EIA cut‐off of 0.8 EIA units was validated, resulting in sensitivity and specificity of 88% and 98.7%, respectively. Conclusion: Our study pioneers and brings important data about the optimization of the Histoplasma antigen testing for the diagnosis of DH in a population from Southern Brazil. This optimization also reduced the amount of reagents used, lowering the cost associated with testing.